Digital Transformation Education for Identifying Future Business Opportunities - Halim, Hendra; Lubis, Muharman; Lubis, Fahdi Saidi; Dawood, Taufiq Carnegie; Majid, M. Shabri Abd.; Amri, Amri; Zulkifli, Zulkifli; Purnami, Ni Made; Nurlina, Eka; Silvia, Vivi (Universitas Syiah Kuala, 2025)
The rapid advancement of digital technology has created a pressing need for digital transformation in various sectors, including entrepreneurship. However, many students and academics still lack adequate understanding and skills to identify future business opportunities through digital approaches. This community service activity, titled Digital Transformation Education for Identifying Future Business Opportunities, was conducted to address this issue. The program involved students and lecturers from Telkom University's Faculty of Industrial Engineering and Syiah Kuala University. Using the Service Learning (SL) approach, the activity was carried out through an online seminar that combined theoretical explanations and interactive discussions with digital business practitioners. Two experts in Islamic economics and information technology served as the resource persons. The activity aimed to increase digital literacy and entrepreneurial awareness among participants. Assessment through pre-test and post-test evaluations revealed a significant improvement in understanding, with the average score increasing from 63.5 to 85.8. The results demonstrate that structured digital transformation education can effectively enhance the capacity of the academic community in identifying and developing digital-based business opportunities. This activity also contributes to the achievement of Sustainable Development Goals (SDGs), particularly in promoting quality education, decent work and economic growth, and fostering innovation.